Conservationists' moral obligations toward wildlife: Values and identity promote conservation conflict. (December 2019) - Bruskotter, Jeremy T.; Vucetich, John A.; Dietsch, Alia; Slagle, Kristina M.; Brooks, Jeremy S.; Nelson, Michael P.
Abstract: Recent debate among scholars reveals potential rifts in the conservation community concerning the moral bases of conservation, and the nature of humanity's obligations to nature. We reasoned that conflict within the conservation community could stem both from divergent values and identification with relevant interest groups. We used secondary data from three recent studies that quantify wildlife value orientations, belief in the intrinsic value of wildlife, and perceived moral obligations to wildlife among US residents and self-identified conservationists. Results indicate the vast majority (>75%) of conservationists both endorse the idea that wildlife possess intrinsic value, and that humans have an obligation to treat wild animals with concern for their welfare – ideas that are consistent with, though not unique to, compassionate conservation. Further, we found that both mutualism value orientations and identification with other interest groups relevant to conservation (e.g., animal rights, hunting) were moderately correlated with beliefs about an individuals' obligations toward wildlife—providing evidence that both values and identity are sources of social conflict within the conservation community. Identity could provide a mechanism linking individual-level, cognitive processes with group-level processes (e.g. immergence) that promote both within-group conformity and between-group conflict, but more research is needed to unravel causality.